2017
DOI: 10.23928/foldt.kozl.2017.147.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Az Endrődi Formáció kőzettani és palinológiai vizsgálata a Hódmezővásárhely–I fúrásban (Makói-árok) — őskörnyezeti és diagenezis-történeti értékelés

Abstract: This paper presents the results of a mineralogical, petrographic and palynological study of selected Pannonian calcareous marl and sandstone samples penetrated by the Hódmezővásárhely-I (Hód-I) well, Endrőd Formation (Tótkomlós Member, cores 35 and 40, 5167.0-5183.0 m and 5468.0-5486.0 m, respectively); this formation is part of the Makó Trough of the Pannonian Basin, SE Hungary. The studied sections comprise mixed carbonate-siliciclastic rocks with abundant silt-to sand-sized angular grains such as monocrysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 35 publications
1
12
0
4
Order By: Relevance
“…The polymictic and highly immature clast composition reflects the importance of local provenance (e.g., recycled detritus derived from erosion of intrabasinal basement highs) during the deposition of the Újfalu and Algyő sediments. Some previous studies [32,37] have also shown carbonate (dolomite, limestone) source components in the underlying Upper Miocene formations (Szolnok and Endrőd).…”
Section: Geofluidsmentioning
confidence: 90%
See 4 more Smart Citations
“…The polymictic and highly immature clast composition reflects the importance of local provenance (e.g., recycled detritus derived from erosion of intrabasinal basement highs) during the deposition of the Újfalu and Algyő sediments. Some previous studies [32,37] have also shown carbonate (dolomite, limestone) source components in the underlying Upper Miocene formations (Szolnok and Endrőd).…”
Section: Geofluidsmentioning
confidence: 90%
“…During the Late Miocene and Early Pliocene, the paleo-Danube and paleo-Tisza Rivers progressively filled it with clastic material sourced by the surrounding mountain chains, creating one of the thickest Neogene nonmarine sedimentary sequences in Europe [28]. The central and deepest (average thickness: 2-3 km, locally up tõ 7 km) depression of the Pannonian Basin is the Great Hungarian Plain, including the studied Szeged area (Figure 2), where the majority of the sediments accumulated [28][29][30]32]. Based on recent calculations [33], the water depth of the lake was more than 1000 m in the deepest subbasins.…”
Section: Geological Setting the Neogene-quaternary Pannonianmentioning
confidence: 99%
See 3 more Smart Citations